Uji Iritasi Krim Hasil Fermentasi Bunga Rosella (Hibiscus sabdariffa L.) Dengan Variasi Konsentrasi Emulgator Novemer Pada Kulit Kelinci (Oryctalagus cuniculus) - Aisyah Fatmawaty, Marianti A Manggau, Rosany Tayeb, Rabiah Al Adawiah (STIFA Makassar, 2016)
The research about irritation test of antioxidant cream from fermented Rosella’s flower infusion using emulgator Novemer has been conducted. This research was aimed to found emulgator Novemer’s concentration that using in the formula of antioxidant cream has the irritation effect on the rabbit’s skin. This research utilized 6 rabbits with the skin has been abraded at the back for a 1-square-inch, those for each irritant sample using 3 formulas of the antioxidant cream I, II, III, (have variation in concentration of emulgator Novemer) and its cream base. The test is measured by patch test by Draize. The results indicate to primary irritation index of the three formulas of antioxidant cream and the cream basics are middle irritating (irritation index 0.5 - 2)